Non-Adherence to Human Rights and Humanitarian Laws in the Conduct of Armed Conflict in Yemen - Mohammed Salem Alqahtani; Rohaida Nordin; Faridah Jalil (Faculty of Law, Sriwijaya University, Indonesia, 2022)
To protect the properties, lives, and dignity of human persons worldwide, the International Humanitarian Law seeks to uphold and promote Human Rights Law and other international frameworks regulating the rights of civilians and parties to armed conflict. The conduct of parties to the armed conflict who have grossly violated the combined provisions of International Human Rights Law and the International Humanitarian Law resulted in the persistence of armed conflict and warfare in Yemen, thereby crossing every access road to humanitarian rights and privileges. The researchers adopt the doctrinal methodology to investigate the status of warfare in Yemen, the provisions of the law on International Human Rights and Humanitarian Law, and the extent to which the parties to the armed conflict in Yemen break such laws. The International Humanitarian Law and the International Human Rights Law regulate the conduct of actors and parties in the armed conflict both in Yemen and the world at large. The finding of this studydemonstrates that all the participants in the conflict in Yemen violate the International Humanitarian Law. Therefore, they are accountable for such violations.The research recommends strict adherence and compliance to both the International Human Rights Law and the Humanitarian Law throughout the armed conflict in Yemen to have lasting peace. Furthermore, accountability for violations committed should be identified, and all actors in the armed conflict should be punished accordingly.